Strange Bedfellows: Nuclear Factor, Erythroid 2-Like 2 (Nrf2) and Hypoxia-Inducible Factor 1 (HIF-1) in Tumor Hypoxia - Rachel K. Toth; Noel A. Warfel (MDPI AG, 2017)
The importance of the tumor microenvironment for cancer progression and therapeutic resistance is an emerging focus of cancer biology. Hypoxia, or low oxygen, is a hallmark of solid tumors that promotes metastasis and represents a significant obstacle to successful cancer therapy. In response to hypoxia, cancer cells activate a transcriptional program that allows them to survive and thrive in this harsh microenvironment. Hypoxia-inducible factor 1 (HIF-1) is considered the main effector of the cellular response to hypoxia, stimulating the transcription of genes involved in promoting angiogenesis and altering cellular metabolism. However, growing evidence suggests that the cellular response to hypoxia is much more complex, involving coordinated signaling through stress response pathways. One key signaling molecule that is activated in response to hypoxia is nuclear factor, erythroid 2 like-2 (Nrf2). Nrf2 is a transcription factor that controls the expression of antioxidant-response genes, allowing the cell to regulate reactive oxygen species. Nrf2 is also activated in various cancer types due to genetic and epigenetic alterations, and is associated with poor survival and resistance to therapy. Emerging evidence suggests that coordinated signaling through Nrf2 and HIF-1 is critical for tumor survival and progression. In this review, we discuss the distinct and overlapping roles of HIF-1 and Nrf2 in the cellular response to hypoxia, with a focus on how targeting Nrf2 could provide novel chemotherapeutic modalities for treating solid tumors.